2011
DOI: 10.1155/2011/178475
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Expression of Superoxide Dismutase-2 Correlates with Different Stages of Cervical Neoplasia

Abstract: Abstract.Objective: Superoxide dismutase-2 (SOD2) is considered one of the most important antioxidant enzymes that regulate cellular redox state in normal and tumorigenic cells. Overexpression of this enzyme may be involved in carcinogenesis, particularly in lung, gastric, colorectal and breast cancer. Methods: In the present study, we have evaluated SOD2 protein levels by immunohistochemistry (IHC) in 331 cervical histological samples including 31 low-grade cervical intraepithelial neoplasia (LSIL), 51 high-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
3
22
1
2
Order By: Relevance
“…was implicated as a tumor suppressor (26), however, more recently, there is accruing evidence that of the oncogenic/tumor-promoting role of SOD2 (13)(14)(15). Consistent with the later, in this study we demonstrated the oncogenic role of the aberrant expression of SOD2 in CRC, as evidenced by its ability to facilitate metastatic disease progression through the repression of hsa-miR-324 (Figure 3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…was implicated as a tumor suppressor (26), however, more recently, there is accruing evidence that of the oncogenic/tumor-promoting role of SOD2 (13)(14)(15). Consistent with the later, in this study we demonstrated the oncogenic role of the aberrant expression of SOD2 in CRC, as evidenced by its ability to facilitate metastatic disease progression through the repression of hsa-miR-324 (Figure 3).…”
Section: Discussionsupporting
confidence: 89%
“…While there are divergent 6 views on the actual role of SOD2 in cancer, there is growing evidence that the loss of SOD2 function may not facilitate metastatic disease progression as previously thought, rather there is indication from experimental and epidemiological studies that enhanced SOD2 expression levels correlates with metastatic malignantization and disease progression in various cancer types (13). It has been shown that the up-regulation of SOD2 protein expression is characteristic of certain cancers, including cervical and salivary adenoid cystic carcinoma (14,15). There is documented correlation or association between down-regulated miRNA expression and tumor initiation or metastatic disease progression (17,18) donkey anti-rabbit IgG were purchased from Invitrogen (Grand Island, NY, USA).…”
Section: (3)mentioning
confidence: 99%
“…In relation to cervical cancer and its precursor lesions, Termini et al [20] examined the expression of SOD2 in a set of cervical samples, including lowgrade squamous intraepithelial lesion (LSIL), HSIL, SCC and ADC. Those authors observed that HSIL and invasive cancers exhibited higher SOD2 levels than LSIL and, in most LSIL samples, they observed no or low SOD2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Superoxide dismutases (SOD) constitute metalloenzymes that act in the context of a cellular antioxidant system and are expressed both in prokaryotic and eukaryotic cells. These proteins protect cellular mechanisms from oxidative stress by converting superoxide radicals into hydrogen peroxide and oxygen (50). There are three members of the family in mammalians.…”
Section: Discussionmentioning
confidence: 99%